ANALISIS PELAKSANAAN FUNGSI BADAN PERMUSYAWARATAN DESA DALAM MELAKUKAN PENGAWASAN KINERJA KEPALA DESA MENDALA KECAMATAN PENINJAUAN KABUPATEN OGAN KOMERING ULU - Maulana Ishaq (Jurnal Riset Multidisiplin Edukasi, 2026)
This research is driven by the significant role of the Village Consultative Body (BPD) as a democratic entity at the village level, tasked with supervising government operations to avert the misuse of authority and community finances. Despite the Head of Mendala Village fulfilling his responsibilities, the oversight system of the BPD is deemed ineffective due to the members' insufficient comprehension of their roles and functions, coupled with inadequate communication that obstructs the expression of community aspirations concerning public facility development. The primary issue of this research is the manner in which the BPD executes its role in overseeing the performance of the Head of Mendala Village in Peninjauan District. The study was carried out from June 19 to July 14, 2025. Employing a descriptive qualitative methodology. Primary data was acquired via interviews with the Chairperson and Members of the Village Consultative Body (BPD), the Village Head, and several village authorities in the Mendala Village Office. The employed data analysis approaches encompassed data reduction, data display, and conclusion formulation. The findings demonstrate that the Mendala Village BPD formulates supervisory criteria grounded in legal documents, including the RPJMDes and APBDes. The measurement phase involves the validation of administrative records (LKPJ/LPJ) and physical verification in the field (sidak) utilizing measuring instruments and checklists. In conclusion, the Mendala Village BPD is failing to execute its supervisory role efficiently and systematically to guarantee accountability in village governance. Recommendations encompass enhancing the digitalization of the information portal for real-time transparency, providing technical training for BPD members in assessing the quality of physical materials, and optimizing deviation analysis in the Minutes of Supervision Results (BAHP) document.